The application of non-deterministic model updating method of a complex jointed structure using central composite design based meta-model - M. A. S., Aziz Shah; M. A., Yunus; M. N., Abdul Rani; M. S. M., Sani (IOP Publishing, 2020)
Finite element (FE) model of a structure is highly depended on idealising and simplification of model, however, the model may not truly represent the physical structure. The application of FE model updating is advocated to modify FE model of structure in order to acquired better correlation between the predicted and measured structure response. Nevertheless, for complex jointed structure, a FE model is containing a very large degree of freedoms that may contribute to high computational time. Therefore, this paper presents the application of response surface method in non-deterministic model updating using central composite design (CCD) sampling for improving the efficiency of a finite element model of a laser stitch welded structure. In this study, FE model of the structure is developed using CQUAD4 shell elements and ACM2 element connectors been used to representing the laser stitch weld joints. For the measured data, experimental modal analysis was performed using LMS SCADAS and conducted under free-free boundary conditions. In the model updating, the minimisation of uncertainties parameters in the FE model is based on the objective function that is formed from the residuals between the FE and experimental natural frequencies. The results show that the response surface method using CCD sampling is efficient to be used in FE model updating because it is capable of improving the accuracy of the initial FE model.